Deconstruction and Subversion in Literature: Countering the Hegemony of Colonial Discourse: Dekonstruksi dan Subversi dalam Sastra: Sebuah Refleksi Perlawanan Terhadap Hegemoni Wacana Kolonial - Rahman, Fadhlur; Kholid, Mohammad (Journal of Literature and Education, 2025)
The traces of colonialism continue to shape the way we think and understand culture, identity and power. This is often through stigmatized ideas of race and simplified distinctions between “us” and “them.” These narratives, rooted in colonial discourse, tend to ignore the complexity of indigenous realities. This research attempts to explore how postcolonial writers challenge and deconstruct these dominant narratives, revealing their political and ideological underpinnings. Drawing on Jacques Derrida’s concept of deconstruction, it examines how contradictions in colonial texts can be exposed and subverted to make room for alternative voices. Through an in-depth analysis of literary works such as The Wretched of the Earth, Season of Migration to the North, 1984, and The Book of Chameleons. The findings of the study highlight how literature becomes a tool of resistance that, through deconstruction and subversion, reshapes identities, reclaims silenced stories, and undermines colonial authority. Equally significant, by demonstrating that meaning is never fixed, the strategies of deconstruction and subversion employed in these works underscore the power of literature to disrupt hegemonic narratives and to open up new, pluralistic perspectives on the complexities of the postcolonial world.